Media Sosial: Wadah Baru Evangelisasi - Bartolomeus Sihite (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Nowadays, we have moved into the second oral era, enlivened by television and information technology. So the 'virtual world' grew which was supported by new tools with all the charming facilities. The changing reality of the world around us is a context that must be taken into account if we want to carry out faith preaching activities. The main problem of preaching in this era is not